Composição química e atividade leishmanicida de extratos de Marsypianthes chamaedrys (Lamiaceae) - MIGNONI, Maria Simone Pereira Maciel (2021)
Leishmaniasis is a disease of great threat to tropical countries, having a high impact on public health in Brazil. It is curable, but the drugs used in its treatment are highly toxic and lead to serious adverse effects, in addition to generating resistance. In this perspective, we sought to evaluate the chemical composition and leishmanicidal activity of Marsypianthes chamaedrys, a plant of the Lamiaceae family, with studies that are still incipient, but promising, as it is used in popular medicine as an anti-inflammatory, and in some studies it has shown analgesic activities, anti-inflammatory, anti-ophidic antiedematogenic, among others. In the first chapter, a theoretical framework was raised in order to explain the general theme of the work, followed by the second chapter with a review of the leishmanicidal activity of species of the Lamiaceae family, which presents extracts, fractions and non-volatile compounds against promastigote and amastigote forms of Leishmania present in the Americas, Africa and Asia. In all, forty-two species of Lamiaceae were found, belonging to twenty-six genera, and ninety-one constituents, isolated from eighteen species of this family, evaluated in in vitro leishmanicidal assays. Chemical and biological aspects of isolated extracts, fractions and constituents were discussed in order to define a profile of the leishmanicidal plants of this family, based on the results observed in in vitro assays. Altogether, there are forty-two species of Lamiaceae, belonging to twenty-six genera, and ninety-one constituents, isolated from eighteen species of this family, evaluated in in vitro leishmanicidal tests. In the third chapter, the ethanol extract of M. chamaedrys and its fractions in dichloromethane (MCF- DM), hexane (MCF-DM) and in ethyl acetate (MCF-AE) were evaluated for leishmanicidal activity against Leishmania amazonensis promastigotes and cytotoxicity against RAW 264.7 macrophages, using the cell viability method with the MTT reagent (3-(4,5-dimethyl-2-thiazol)-2,5-diphenyl-tetrazolium bromide). The chemical composition of the best fraction was obtained by HPLC-DAD. The extract and its fractions inhibited the promastigote forms of L. amazonesis, with a better leishmanicidal action in the MCF-DM fraction (IC50 = 17.90 ± 1.172 μg/mL) in in vitro assays. This same MCF-DM fraction (CC50 >100) was effective in the cytotoxic evaluation against RAW 264.7 cells and demonstrated a better selectivity index (IS>5.5). The chemical analysis of the fraction in dichloromethane by HPLC-DAD identified, in comparison with the standard, two constituents, a major one with a peak area of 35%, this being rosmarinic acid, and a second compound, caffeic acid with 5%, being that the latter is identified for the first time in the species, in addition to 15 compounds in smaller quantities, which have UV spectra with an absorption profile compatible with phenolic compounds. The results allow us to conclude that the MCF-DM fraction has leishmanicidal potential, low cell toxicity, high concentration of phenolic compounds, and may provide a promising chemical model for future studies aimed at the development of leishmanicidal therapies.